Empowering Postdoctoral Scholars: Insights From Library Focus Groups - Bohman, Lena; Hertz, Marla I; Vitiello, Regina (Evidence Based Library and Information Practice, 2025)
Objective – The goal of this study was to assess how postdoctoral scholars (postdocs) engage with the campus library and identify barriers to access. Postdocs occupy a unique position within the research community, bridging the gap between graduate studies and permanent academic positions. Despite their critical role, there has been little formal research to examine how postdocs interact with library resources and services, likely due in part to their relatively small numbers at academic and research institutions.Methods – Three focus group interviews were conducted at two research intensive institutions in the United States. The qualitative analysis employed an iterative coding process to explore several themes: self-proclaimed needs to succeed during postdoctoral training; perceptions of library offerings, including space, services, and collections; and barriers to success.Results – The thematic analysis revealed that postdocs value library resources and are seeking a range of services including financial services, mentorship, and scholarly writing support. There were only minor differences observed between the two institutions. The study identified lack of communication and time as the main barriers postdocs cited for not using the library. Based on participant feedback, we developed recommendations to enhance the postdoctoral experience with library resources and support their career development.Conclusion – This study contributes valuable insights into optimizing library services for postdocs and highlights opportunities for libraries to better align their offerings with the unique needs and challenges faced by this sector of the academic community. Our approach also serves as a model to assess and improve library offerings to other small communities.